Pengaruh Kualitas Pelayanan dan E-Promotion terhadap Keputusan Pembelian pada Outlet Cafe Eat Toast di Indramayu - Nurul Azizah; Danang Kusnanto (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to examine and analyze the influence of service quality and e-promotion on purchasing decisions at Cafe Eat Toast Outlets in Indramayu. This research was conducted using quantitative research methods with descriptive and verification analysis, namely collecting, presenting, analyzing and testing hypotheses, as well as making conclusions and suggestions. The sample in this study amounted to 285 respondents by using the sampling technique Accidential Sampling. The data analysis technique used is Likert scale analysis technique and path analysis. The partial effect of service quality on purchasing decisions is 22.8%, while e-promotion on purchasing decisions has a greater influence and contribution, which is 39.6%. Simultaneously, the total influence of service quality and e-promotion on purchasing decisions is 31.3% while the remaining 68.7% is the contribution of other variables not examined.